2015
DOI: 10.3892/ijo.2015.3143
|View full text |Cite
|
Sign up to set email alerts
|

miR-873 acts as a novel sensitizer of glioma cells to cisplatin by targeting Bcl-2

Abstract: Treatment with cisplatin, a chemotherapeutic agent commonly used in glioma patients, often results in chemoresistance. Increasing evidence has shown that microRNAs (miRNAs) are implicated in the drug resistance of gliomas. However, the function of miR‑873 in cisplatin resistance of gliomas remains unknown. In this study, we found that many miRNAs, including miR‑873, are differentially expressed in cisplatin-resistant glioma cells compared to wild-type glioma cells. Moreover, cisplatin reduced the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 26 publications
3
32
0
Order By: Relevance
“…Recent studies have found that miRNAs regulate drug resistance by mediating their targeting genes in various cancers . In recent years, abnormal expression of miR‐873 has been found in many kinds of tumors, such as breast and ovarian cancers, and glioma . MiR‐873 plays a role in promoting cancer or anticancer by regulating tumor cell invasion, migration, proliferation, apoptosis, and sensitivity to chemotherapeutic drugs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have found that miRNAs regulate drug resistance by mediating their targeting genes in various cancers . In recent years, abnormal expression of miR‐873 has been found in many kinds of tumors, such as breast and ovarian cancers, and glioma . MiR‐873 plays a role in promoting cancer or anticancer by regulating tumor cell invasion, migration, proliferation, apoptosis, and sensitivity to chemotherapeutic drugs .…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24] In recent years, abnormal expression of miR-873 has been found in many kinds of tumors, such as breast and ovarian cancers, and glioma. [25][26][27] MiR-873 plays a role in promoting cancer or anticancer by regulating tumor cell invasion, migration, proliferation, apoptosis, and sensitivity to chemotherapeutic drugs. [28][29][30][31] Nevertheless, the role of miR-873 in drug resistance in NSCLC is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence has shown that miRNAs also plays a vital role in chemotherapeutic resistance. For instance, miR‐873 was found to improve the chemosensitivity of glioblastoma cells to cisplatin by targeting Bcl‐2 . MiR‐16 was reported to mediate TMZ resistance in glioma cells by modulation of apoptosis , highlighting miRNAs as potent chemo‐resistant modulators in the treatment of glioma.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (10) further demonstrated that miR-873 reverses the EMT in colon cancer by negatively regulating the expression of ZEB1. This miRNA has also been reported to be downregulated in glioma tissues and to enhance chemoresistance to cisplatin by targeting Bcl-2 (19). However, another study revealed that miR-873 expression is upregulated in lung adenocarcinoma, and that this miRNA increases the proliferation and metastasis of these cells by regulating the tumor suppressor gene SRCIN1 (15).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also revealed that abnormal expression of miR-873 occurs in various types of cancer, such as breast, lung, colorectal and ovarian cancer, and glioma (9)(10)(11)(12)(13)(14)(15)(16)(17). Notably, miR-873 is crucial for paclitaxel and cisplatin sensitivity in ovarian cancer and cisplatin sensitivity in glioma (18,19). However, the expression and function of miR-873 in cervical cancer are not fully understood.…”
Section: Introductionmentioning
confidence: 99%